PERCUTANEOUS CORONARY INTERVENTION FOR CHRONIC TOTAL OCCLUSION: EXPERIENCE AT ARMED FORCES INSTITUTE OF CARDIOLOGY - Khattak, Zahoor Aslam; Khan, Nadir; Khan, Muhammad Qaiser; Samore, Naseer Ahmed; ., Adeel; Aziz, Sohail (Pakistan Armed Forces Medical Journal, 2015)
Objective: To evaluate the procedural outcome of patients having Chronic Total Occlusion (CTO) undergoing Percutaneous Coronary Intervention (PCI) at our clinical setup. Study Design: Descriptive cross sectional study. Place and Duration of Study: This study was conducted at AFIC/NIHD Rawalpindi from Feb 2012 to Dec 2013. Material and Methods: A total of 50 patients who underwent PCI for CTO were included in our study. Patients with CTO lesion ≥3 months were included in our study. All the patients were selected by nonprobability sampling technique. Patient’s demographic data and data regarding procedural outcome was recorded. Finally data was analyzed using descriptive statistics. Results: Out of 50 patients 43 were male while 7 were female with male to female ratio of 1:6.14. Age range of the patient was 38-82 years with mean age of 64.72±8.52. The mean estimated duration of occlusion was 15±10 months. Major contributing risk factors were diabetes, hypertension, hyperlipidemia, smoking, positive family history, prior myocardial infarction and chronic hemodialysis. In 23 (46%) LAD was involved, in 7 (14%) LCx while in 20 (40%) patient RCA was involved. Procedural success was achieved in 49 (98%) patients while in 1(2%) patient it was unsuccessful. The failure of procedure is due to inability of wire to cross the CTO lesion. Thus overall procedural success was achieved in 98% patients. Conclusion: The recanalization of CTO lesion was successfully done in 98% cases using PCI. However 2% cases were unsuccessful due to failure of guide wire to cross the lesion.